The level and components of asthenia among interns in the specialty «Psychiatry» in conditions of psychosocial crisis. Ogorenko V.V., Shusterman T. Y., Nikolenko A.Ye., Kokashynskyi V. O. - Ogorenko Вікторія; Shusterman Тамара; Nikolenko Алла; Kokashynskyi Віктор (Psychosomatic Medicine and General Practice, 2024)
Introduction. Asthenia (from Greek Asthenia – weakness) is a psychopathological condition characterized by weakness, increased fatigue, emotional lability, hyperesthesia, sleep disorders. In the population, the frequency of chronic form of asthenia or chronic fatigue syndrome reaches 2,8%. Stress loads are the everyday reality of a modern person, in particular in the conditions of a military conflict, the psychological consequences of the COVID-19 pandemic, etc. The risk group for the consequences of a psychosocial crisis is medical workers, in particular specialists of psychiatric services. The problem of asthenia among medical interns is an actual one that requires further study and resolution, especially in the conditions of a psychosocial crisis. The purpose of the study is to identify and assess the level and components of asthenia among interns specializing in «Psychiatry» in conditions of a psychosocial crisis. Methods. A psychodiagnostic study of the level and components of asthenia in 30 interns in the specialty «Psychiatry» of the 1st and 2nd years of study was carried out, using the psychometric scale for assessing the level of fatigue (Fatigue Assessment Scale, FAS). Results. The asthenia score among the entire sample indicated the presence of fatigue (moderate level of asthenia), and fatigue was observed among both male and female. In the conducted study, it was found that the level of physical asthenia prevailed over the level of mental one in the entire sample, and this tendency was noticeable among both male and female. When assessing the severity/level of asthenia, the following has been found: absence of asthenia was observed among 10,0% of participants, presence of fatigue (mild or moderate level) - 66.7%, and pronounced fatigue (high level) was present among 23,3% of participants. In particular, the absence of fatigue was noted by 11,1% of male, the presence of fatigue by 77.8%, pronounced fatigue by 11,1%. Among female, 9.5% noted the absence of fatigue, 61.9% - the presence of fatigue, and 28.6% - pronounced fatigue. Discussion. Our results regarding the moderate level of asthenia in psychiatry interns coincide with the data of other researchers regarding the increased risk of emotional burnout syndrome among young doctors. As mentioned in a number of studies, training young doctors in practices to cope with the effects of fatigue can help prevent the early development of burnout syndrome. In order to mitigate the signs of fatigue and burnout among medical workers, in particular psychiatric services, it is necessary to develop strategies and programs for the prevention and prevention of the consequences of the psychosocial crisis in the health care system. Conclusion. All study participants have showed fatigue, which corresponded to a moderate level of asthenia, both among male and female. According to the components of asthenia, it has been established that the level of physical asthenia prevailed over the level of mental asthenia, in all participants of both sexes. According to the level of asthenia and the degree of severity, no statistically significant difference was found between female and male in the sample. The obtained data should be taken into account when conducting early diagnosis, prevention and correction of asthenic manifestations in interns in the specialty «Psychiatry», to prevent the syndrome of professional burnout, in particular in conditions of psychosocial crisis.